2007
DOI: 10.1063/1.2743385
|View full text |Cite
|
Sign up to set email alerts
|

H 2 S exposure of a (100)Ge surface: Evidences for a (2×1) electrically passivated surface

Abstract: The experimental study of the bonding geometry of a (100)Ge surface exposed to H2S in the gas phase at 330°C shows that 1 ML S coverage with (2×1) surface reconstruction can be achieved. The amount of S on the Ge surface and the observed surface periodicity can be explained by the formation of disulfide bridges between Ge–Ge dimers on the surface. First-principles molecular dynamics simulations confirm the preserved (2×1) reconstruction after dissociative adsorption of H2S molecules on a (100)Ge (2×1) surface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 14 publications
5
49
0
Order By: Relevance
“…For pMOSFETs, germanium is identified as a particular good candidate [2] and many passivation routes have been proposed by introducing different Ge-high K interlayers: GeO 2 [3], GeON [4], S [5], Sr [6] and ultrathin Si cap [7][8][9]. The latter passivation scheme permits to introduce Si back into Ge MOSFET processing as a well-known starting surface for high K-metal gate stack deposition.…”
Section: Introductionmentioning
confidence: 99%
“…For pMOSFETs, germanium is identified as a particular good candidate [2] and many passivation routes have been proposed by introducing different Ge-high K interlayers: GeO 2 [3], GeON [4], S [5], Sr [6] and ultrathin Si cap [7][8][9]. The latter passivation scheme permits to introduce Si back into Ge MOSFET processing as a well-known starting surface for high K-metal gate stack deposition.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, researchers continue to look for alternative passivation schemes. Sulfur passivation [73,74] combined with Al 2 O 3 [75,76] is an attractive solution since it provides good passivation for both Ge and InGaAs surfaces [76] and therefore makes it a prospective candidate for a common passivation/gate dielectric scheme in dual channel CMOS.…”
Section: Extrinsic Defects and Passivation Of The Germanium Surface Amentioning
confidence: 99%
“…Recently, it has been reported that passivation of the defects by injecting sulfur ions into Ge, is effective in improving the electrical properties . Along with a conventional wet process in which the Ge substrate is immersed in aqueous (NH 4 ) 2 S, a dry process in which the Ge substrate is exposed to H 2 S gas environment with heat, is newly developed . The S ions injected by these methods have been simply regarded as to fill the defects by occupying the oxygen sites or form Ge–S bonding at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…The S ions injected by these methods have been simply regarded as to fill the defects by occupying the oxygen sites or form Ge–S bonding at the interface. In both cases, the S ions should have valence of –2 similar to O ions . However, the S ions incorporated in the high‐ k GI layers can, in principle, be further oxidized due to abundance of oxygen ions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation